Population structure and resistance to metalaxyl in isolates of Phytophthora infestans - V.S. PUNDHIR, VAIBHAV K. SINGH* and (Indian Phytopathology, 2013)
Phytophthora infestans isolates were collected from local areas of Pantnagar during 2005-07 cropping season and analyzed for identification of physiological races by using twenty host differential sets. Among the 16 isolates of P. infestans tested occurrence of seven different high spectrum physiologic races was established. These races were 1.2.4.6.7.11 with 6 gene complex, 1.2.3.4.8.10.11 and 1.2.3.7.8.10.11 with 7 gene, 1.2.3.4.5.7.8.10 and 1.2.3.4.7.8.10.11 with 8 gene, 1.2.3.4.6.7.8.9.10 with 9 gene and 1.2.3.4.5.6.7.8.9.10 with 10 gene complex. P. infestans isolates of potato cultivar Kufri Bahar showed the race 1.2.3.4.5.6.7.8.9.10 with 10 gene complex while other three potato cultivars (Kufri Badshah, Kufri Jawahar and Kufri Sutlej) showed race 1.2.3.4.5.7.8.10 with 8 gene complex. No oospores were formed on pairings of any of the P. infestans isolates of four potato cultivars for identification of mating type, indicating that all the isolates belonged to A1 mating type. Resistance to metalaxyl gave positive results as all the P. infestans isolates exhibited Met-resistance at 100 ppm showing >70% growth as compared to control.